2008
DOI: 10.1038/sj.bjc.6604758
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study examining tamoxifen adherence and its relationship to mortality in women with breast cancer

Abstract: Increasing duration of tamoxifen therapy improves survival in women with breast cancer but the impact of adherence to tamoxifen on mortality is unclear. This study investigated whether women prescribed tamoxifen after surgery for breast cancer adhered to their prescription and whether adherence influenced survival. A retrospective cohort study of all women with incident breast cancer in the Tayside region of Scotland between 1993 and 2002 was linked to encashed prescription records to calculate adherence to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
258
7
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(300 citation statements)
references
References 29 publications
19
258
7
5
Order By: Relevance
“…Non-adherence to treatment recommendations have been shown to correlate with lower cancer survivals in previous studies cancers (Li et al, 2000;Herbert-Croteau et al, 2004;McCowan et al, 2008;Wockel et al, 2010 a, b ; Hershman et al, 2011). While the statistical power available to demonstrate similar associations in the present study was very low due to small numbers, point estimates were suggestive of higher case fatalities when treatments were declined.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Non-adherence to treatment recommendations have been shown to correlate with lower cancer survivals in previous studies cancers (Li et al, 2000;Herbert-Croteau et al, 2004;McCowan et al, 2008;Wockel et al, 2010 a, b ; Hershman et al, 2011). While the statistical power available to demonstrate similar associations in the present study was very low due to small numbers, point estimates were suggestive of higher case fatalities when treatments were declined.…”
Section: Discussionsupporting
confidence: 48%
“…Adherence to recommended treatments has been linked to higher disease-free and overall survival for breast and other cancers (Li et al, 2000;Herbert-Croteau et al, 2004;McCowan et al, 2008;Wockel et al, 2010a,b;Hershman et al, 2011). Non-adherence can be a result of many clinical factors including treatment compromises to accommodate patient frailty or co-morbidity, clinician preference, poor service access or high user cost Lebeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that approximately 1 in 5 adjuvant tamoxifen users fail to achieve an optimal adherence threshold of 80% or greater during the first year of treatment, and there is a 7% to 10% discontinuation rate per year (12,14,15). By year 4 or 5 of treatment, the full adherence rate drops to 50% (14,16).…”
Section: Early Disease/adjuvant Therapymentioning
confidence: 98%
“…By year 4 or 5 of treatment, the full adherence rate drops to 50% (14,16). Similarly, nonpersistence with adjuvant tamoxifen is about 20% to 30% at year 1 or 2 (15,17,18) and climbs to as high as 49% before the completion of 5 years (15,16,19). Available data on the association between adherence to adjuvant tamoxifen therapy and breast cancer outcomes have suggested that poor tamoxifen adherence contributes to therapeutic failure with an increased risk for poor outcomes.…”
Section: Early Disease/adjuvant Therapymentioning
confidence: 99%
“…The majority of studies on medication compliance in oncology have focused on oral hormonal therapies in breast cancer 5, 6, 11, 12, 13 even though oral drugs are also frequently used in other cancers 14, 15, 16, 17. In colon cancer, the oral 5‐fluorouracil prodrug known as capecitabine is a commonly prescribed component in a large number of systemic therapy regimens 18, 19, but it has received relatively little focus to date 20, 21, 22, 23.…”
Section: Introductionmentioning
confidence: 99%